Is genetic drift to blame for testicular dysgenesis syndrome in Semliki chimpanzees (Pan troglodytes schweinfurthii)?. Issue 4 (25th May 2018) - Rich, Alicia M.; Wasserman, Michael D.; Deimel, Caroline; Breeden, Scott K.; Kaestle, Frederika; Hunt, Kevin D.
Abstract: Background: We present 3 likely cases of testicular dysgenesis syndrome (TDS) within a community of chimpanzees ( Pan troglodytes schweinfurthii ). We tested whether genetic drift may be the culprit, as a genetic cause has been suspected to account for TDS among other wildlife. Methods: We successfully sequenced a 367‐bp segment spanning the first hypervariable region within the D‐loop of the mitochondrial genome for 78 DNA samples. Results: We found 24 polymorphic sequence sites consisting of 7 singletons and 17 parsimony informative sites. This sample contained 9 haplotypes with a diversity index of 0.78 (SD = 0.03). All tests against the null hypothesis of neutral polymorphisms were non‐significant ( P > .10). The mismatch distribution of pairwise differences does not fit a Poisson's curve (raggedness index = 0.166; SSD = 0.12; P = 1). Conclusions: Thus, we found no significant signs of genetic isolation, population expansion, or genetic bottleneck. Alternative causes of TDS and how they might pertain to this population are discussed.